AN EVALUATION OF ENGLISH FOR SPECIFIC PURPOSES COURSES AT A VIETNAMESE UNIVERSITY - Duyen, Tran Thi; Tue, Hoang Ngoc; Giang, Le Thi Huong; Nhung, Vu Thi; Hai Hang, Cao Thi (VNU Journal of Foreign Studies; Vol 35 No 5DO - 10.25073/2525-2445/vnufs.4419, 2019)
When English is commonly used in different professional fields and serves as an important communication tool at work, the teaching of English for Specific Purposes at higher education institutions requires more attention. Aiming to increase the effectiveness of ESP education, this study investigates the teaching of ESP courses at a Vietnamese university, evaluating the syllabus, materials, teaching methodology and tests of ESP courses. Data were collected from the questionnaires distributed to 657 ESP students, interviews with 8 ESP teachers and observing ESP lessons delivered by 5 teachers and analysing related documents. Research findings pinpoint the strengths and weaknesses of the ESP courses and propose practical solutions to improve the effectiveness of the courses. The findings could be used as a reference for other higher education institutions with similar educational contexts in Vietnam.